Value Chain Map of Bali Sardinella (Tamban) in Bulan, Sorsogon - Jakim Timothy F. Golimlim (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Fishery is an essential part of food security and livelihood among the Filipino people. This study described the value chain map of Tamban, the challenges encountered by the stakeholders that adversely affect its production, recommended measures to address those challenges, and proposed strategies towards its commercialization in Bulan, Sorsogon. The study employed both quantitative and qualitative data gathering procedures to produce an in-depth data for better analysis. Executed through using survey questionnaire and semi-structured interview, and official document analysis. Tamban is commonly sold to consumers and business in both fresh and processed forms such as dried, smoked, and canned. There are sixty-eight large-scale fish traders, and thirteen small-scale processors; nine for drying, three for smoking, and one for canning. The analysis demonstrates that the largest financial value-added net of cost was realized at the level of processors of fresh to be delivered to wet market for PHP 81.29 during the peak season and PHP 79.85 in lean season. Stakeholders face two major issues: the seasonality and fluctuating catch and the significant losses occurring in peak season. Negotiate fixed-rate/price range, annual contracts for essential supplies like ice, salt, fuel, and plastic bag. Create an emergency stockpile to cushion producers against sudden price shocks. A roadmap to meeting the set goals—minimize errors, idle time, hazards, cost, waste, and maximize opportunities, production, yield, sales, revenue, and efficiency is proposed.